Human Umbilical Cord Blood Cells or Estrogen may be Beneficial in Treating Heatstroke - Sheng-Hsien Chen; Kuo-Feng Huang; Mao-Tsun Lin; Fong-Ming Chang (Elsevier, 2007)
This current review summarized animal models of heatstroke experimentation that promote our current knowledge of therapeutic effects on cerebrovascular dysfunction, coagulopathy, and/or systemic inflammation with human umbilical cord blood cells (HUCBCs) or estrogen in the setting of heatstroke. Accumulating evidences have demonstrated that HUCBCs provide a promising new therapeutic method against neurodegenerative diseases, such as stroke, traumatic brain injury, and spinal cord injury as well as blood disease. More recently, we have also demonstrated that postor pretreatment by HUCBCs may resuscitate heatstroke rats with by reducing circulatory shock, and cerebral nitric oxide overload and ischemic injury. Moreover, CD34+ cells sorted from HUCBCs may improve survival by attenuating inflammatory, coagulopathy, and multiorgan dysfunction during experimental heatstroke. Many researchers indicated pro(e.g. tumor necrosis factor-α [TNF-α]) and anti-inflammatory (e.g. interleukin-10 [IL-10]) cytokines in the peripheral blood stream correlate with severity of circulatory shock, cerebral ischemia and hypoxia, and neuronal damage occurring in heatstroke. It has been shown that intravenous administration of CD34+ cells can secrete therapeutic molecules, such as neurotrophic factors, and attenuate systemic inflammatory reactions by decreasing serum TNF-α but increasing IL-10 during heatstroke. Another line of evidence has suggested that estrogen influences the severity of injury associated with cerebrovascular shock. Recently, we also successfully demonstrated estrogen resuscitated heatstroke rats by ameliorating systemic inflammation. Conclusively, HUCBCs or estrogen may be employed as a beneficial therapeutic strategy in prevention and repair of cerebrovascular dysfunction, coagulopathy, and/or systemic inflammation during heatstroke.